Quercitrin neutralizes sPLA2IIa activity, reduces the inflammatory IL-6 level in PC3 cell lines, and exhibits anti-tumor activity in the EAC-bearing mice model - P. Sophiya; Deepadarshan Urs; Jafar K. Lone; A. S. Giresha; H. Krishna Ram; J. G. Manjunatha; Hamed A. El-Serehy; M. Narayanappa; J. Shankar; Ragini Bhardwaj; Sameer Ahmad Guru; K. K. Dharmappa (Frontiers Media S.A., 2022)
Human phospholipase A2 group IIa (sPLA2IIa) is an inflammatory enzyme that plays a significant role in tumorigenesis. Inhibiting the sPLA2IIa enzyme with an effective molecule can reduce the inflammatory response and halt cancer progression. The present study evaluates quercitrin, a biflavonoid, for sPLA2IIa inhibition and anticancer activity. Quercitrin inhibited sPLA2IIa activity to a greater extent-at 86.24% ± 1.41 with an IC50 value of 8.77 μM ± 0.9. The nature of sPLA2IIa inhibition was evaluated by increasing calcium concentration from 2.5 to 15 µM and substrate from 20 to 120 nM, which did not alter the level of inhibition. Intrinsic fluorescence and far UV-CD studies confirmed the direct interaction of quercitrin with the sPLA2IIa enzyme. This significantly reduced the sPLA2IIa-induced hemolytic activity and mouse paw edema from 97.32% ± 1.23-16.91% ± 2.03 and 172.87% ± 1.9-118.41% ± 2.53, respectively. As an anticancer activity, quercitrin reduced PC-3 cell viability from 98.66% ± 2.51-18.3% ± 1.52 and significantly decreased the IL-6 level in a dose-dependent manner from 98.35% ± 2.2-37.12% ± 2.4. It increased the mean survival time (MST) of EAC-bearing Swiss albino mice from 30 to 35 days. It obeyed Lipinski's rule of five, suggesting a druggable property. Thus, all the above experimental results were promising and encouraged further investigation into developing quercitrin as a therapeutic drug for both inflammatory diseases and cancers.